2017
DOI: 10.5194/acp-17-1453-2017
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of highly oxidized organosulfates and BSOA marker compounds during the F-BEACh 2014 field study

Abstract: Abstract. The chemical composition of ambient organic aerosols was analyzed using complementary mass spectrometric techniques during a field study in central Europe in July 2014 (Fichtelgebirge – Biogenic Emission and Aerosol Chemistry, F-BEACh 2014). Among several common biogenic secondary organic aerosol (BSOA) marker compounds, 93 acidic oxygenated hydrocarbons were detected with elevated abundances and were thus attributed to be characteristic for the organic aerosol mass at the site. Monoterpene measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 87 publications
1
65
0
Order By: Relevance
“…In this study, a similar analysis indicates that 51–57% of OSs existed with corresponding CHO− compounds with multiple hydroxyl groups (Table ), similar to what was observed in Bakersfield (O'Brien et al, ) but slightly lower than those in the Pearl River Delta Region and Taiwan (Lin et al, ), suggesting that the epoxide formation pathway is an important formation route for the OSs observed in urban Shanghai. Recently, a direct formation of OSs from HOMs and/or peroxyradicals was suggested (Brüggemann et al, ). Because a number of HOMs were detected in all Shanghai samples, as discussed earlier, the direct formation mechanism may have also played a significant role in OS formation in addition to the epoxide formation pathway.…”
Section: Resultsmentioning
confidence: 91%
“…In this study, a similar analysis indicates that 51–57% of OSs existed with corresponding CHO− compounds with multiple hydroxyl groups (Table ), similar to what was observed in Bakersfield (O'Brien et al, ) but slightly lower than those in the Pearl River Delta Region and Taiwan (Lin et al, ), suggesting that the epoxide formation pathway is an important formation route for the OSs observed in urban Shanghai. Recently, a direct formation of OSs from HOMs and/or peroxyradicals was suggested (Brüggemann et al, ). Because a number of HOMs were detected in all Shanghai samples, as discussed earlier, the direct formation mechanism may have also played a significant role in OS formation in addition to the epoxide formation pathway.…”
Section: Resultsmentioning
confidence: 91%
“…Most single-particle instruments, e.g., ATOFMS (Gard et al, 1997), SPLAT (Zelenyuk and Imre, 2005), and PALMS (Murphy et al, 2006), utilize simultaneous laser desorption/ionization, which is not quantitative due to matrix effects and can also result in fragmentation of organic molecules. In contrast, the Aerodyne aerosol mass spectrometer (AMS) utilizes a high vaporization temperature (600 • C) and electron ionization (EI, 70 eV) to remain quantitative but at the cost of extensive thermal decomposition and ionization-induced fragmentation (Canagaratna et al, 2007). More recently, the chemical analysis of aerosol on-line particle inlet coupled to a proton transfer reaction time-of-flight mass spectrometer (CHARON-PTR) couples an aerodynamic particle lens with a heated inlet and a softer ionization scheme (via proton transfer reaction, PTR) for measurements of particles between 100 and 750 nm (Eichler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to aerosol acidity, liquid water content (LWC) was shown to play a key role in OS formation, as demonstrated by studies on the aqueous-phase and heterogeneous OS formation mechanisms (McNeill 2015;McNeill et al 2012). As well as the laboratory studies, a large number of such OS species has also been found in ambient aerosol particles collected at remote, urban, forested, marine and arctic sampling sites (Brüggemann et al 2017;Glasius et al 2018b;Iinuma et al 2007a; Kristensen and Glasius 2011;Ma et al 2014;Mutzel et al 2015;Surratt et al 2008), which supported the proposed formation of OSs from mixed biogenic and anthropogenic emissions, and established OSs as SOA marker compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Through condensation or nucleation, such oxidised organic compounds form secondary organic aerosols (SOAs), which commonly contribute up to 50À85 % of the organic fraction of ambient aerosol particles (Glasius and Goldstein 2016). Among these compounds, organosulfates (OSs) have been found to be ubiquitously abundant in ambient aerosol particles (Brüggemann et al 2017;Iinuma et al 2007a; Kristensen and Glasius 2011;Riva et al 2016b;Surratt et al 2008).…”
Section: Introductionmentioning
confidence: 99%